1996
DOI: 10.1002/(sici)1096-9926(199607)54:1<27::aid-tera4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal alcohol use and risk of orofacial cleft birth defects

Abstract: Maternal alcohol use during pregnancy is a known cause of birth defects associated with the fetal alcohol syndrome, but its role in more common, isolated, craniofacial birth defects is not well understood. A population‐based, case‐control study of orofacial clefts was conducted in Iowa using births during 1987–1991. Cases were identified by the Iowa Birth Defects Registry and classified as having a cleft lip with or without cleft palate (CLP) or cleft palate only (CP) and whether the cleft was isolated or occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 21 publications
1
67
1
4
Order By: Relevance
“…Drugs which interfere with folate metabolism, such as phenytoin, are known to have teratogenic effects which include oral cleft, growth retardation, limb defects, and other craniofacial deformities. Maternal intake of vasoactive drugs which include pseudoephedrine, aspirin, ibuprofen, and amphetamine as well as cigarette smoking has been associated with higher risk of oral clefts [34][35][36]. Anticonvulsant medications such as phenobarbital, trimethadione, valproate, and Dilantin have also been documented to increase incidence of cleft lip/cleft palate [37,38].…”
Section: Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs which interfere with folate metabolism, such as phenytoin, are known to have teratogenic effects which include oral cleft, growth retardation, limb defects, and other craniofacial deformities. Maternal intake of vasoactive drugs which include pseudoephedrine, aspirin, ibuprofen, and amphetamine as well as cigarette smoking has been associated with higher risk of oral clefts [34][35][36]. Anticonvulsant medications such as phenobarbital, trimethadione, valproate, and Dilantin have also been documented to increase incidence of cleft lip/cleft palate [37,38].…”
Section: Causesmentioning
confidence: 99%
“…It has been suggested that maternal folic acid supplementation plays a role in the prevention of non-syndromic orofacial clefts, that is, cleft lip with or without cleft palate (CL ± P) [81]. Several studies have reported decreased rates of cleft lip and palate with folic acid use [82][83][84][85]. Some ambiguity of the studies may be explained by a recent study that found that oral cleft risk can be reduced only by high doses of folic acid consumed at the time of lip and palate formation [86].…”
Section: Medical Managementmentioning
confidence: 99%
“…Although experimental models have shown the association between alcohol and birth defects like orofacial clefts, these findings are obscure in humans. Munger et al (1996) studied the influence of alcohol intake and the occurrence of malformations, conducting a population-based case-control investigation. Adjusting the model obtained by variables like family income, maternal education, smoking, vitamins, child's age, and year of birth, they observed an increasing risk gradient with increased consumption of alcohol doses/ month for cases of CL/P, where for the highest doses consumed the OR was statistically significant (4.0; 95% CI: 1.1-15.1).…”
Section: Alcoholmentioning
confidence: 99%
“…Some of the environmental factors implicated in the causation of nonsyndrolnic oral clefts include tobacco use [for all types of clefts (2)(3)(4)(5) and also for CL(P) (3,4)], antiepileptic drugs (6,7), and possibly alcohol consumption [for CL(P)] (8,9). Debate continues as to whether multivitamin supplements, especially folic acid, can prevent oral clefts (10)(11)(12).…”
mentioning
confidence: 99%